BIOLOGIA REPRODUCTIVA DE Armadillidium vulgare (Latreille, 1884) y Armadillidium nasatum (Schultz, 1961) (CRUSTACEA, ONISCIDEA) EN CULTIVO DE MAIZ, URUGUAY - Waller, Analisa; Verdi, Ana (Boletín de la Sociedad Zoológica del Uruguay, 2018)
Reproductive biology of Armadillidium vulgare (Latreille, 1884) and Armadillidium nasatum (Schultz, 1961) (Crustacea, Oniscidea) in corn crop, Uruguay. Armadillidium vulgare (Latreille, 1884) and Armadillidium nasatum (Schultz, 1961) are among the most common species of terrestrial isopods in Uruguay. The reproductive pattern of these species was studied, for first time, on a cultived population at Department of San Jose (Uruguay) from June 2010 to July 2011. A total of 862 individuals were sampled, of these 515 were A. vulgare and 247 were A.nasatum. Adults and juveniles of both species appeared from February to September, and disappeared from October to January. For both species ovigerous females were collected only in February, this would indicate a seasonal reproduction followed by a sexual rest. In A. vulgare reproductive females cephalothorax width ranged between 1.7 to 2,7 mm, average fecundity was equal to 37 ± 5 eggs and average fertility was equal to 28 ± 4 embryos. Fecundity and fertility were positively correlated with the size of the females. In A. nasatum cephalothorax width of reproductive females oscillated between 1.5 to 2.4 mm, no relationship could be established due to the fact that only 3 females with 20 eggs each, 1 female (CW: 2.4 mm) with 22 embryos were registered.